2022
DOI: 10.1038/s41522-022-00342-8
|View full text |Cite
|
Sign up to set email alerts
|

The hallmarks of dietary intervention-resilient gut microbiome

Abstract: Maintaining equilibrium of the gut microbiome is crucial for human health. Diet represents an important and generally accessible natural channel of controlling the nutrients supply to the intestinal microorganisms. Although many studies showed that dietary interventions can specifically modulate gut microbiome composition, further progress of the approach is complicated by interindividual variability of the microbial community response. The reported causes of this variability include the baseline microbiome co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 70 publications
2
20
0
1
Order By: Relevance
“…28 A negative correlation between the average number of genes per microbe and alpha diversity was found, suggesting that more diverse communities are formed by specialist microbes with fewer genes. 28 The microbiomes associated with industrialized countries, like the United States, often have reduced diversity and a higher abundance of Bacteroides when compared to non-industrialized countries. 29 Many Bacteroides are generalists, meaning they contain more genes and wider metabolic potentials than specialist taxa.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…28 A negative correlation between the average number of genes per microbe and alpha diversity was found, suggesting that more diverse communities are formed by specialist microbes with fewer genes. 28 The microbiomes associated with industrialized countries, like the United States, often have reduced diversity and a higher abundance of Bacteroides when compared to non-industrialized countries. 29 Many Bacteroides are generalists, meaning they contain more genes and wider metabolic potentials than specialist taxa.…”
Section: Discussionmentioning
confidence: 96%
“…28 Klimenko et al found that the strongest predictor of whether an individual would respond to a dietary intervention was the average number of genes per microbe. 28 A negative correlation between the average number of genes per microbe and alpha diversity was found, suggesting that more diverse communities are formed by specialist microbes with fewer genes. 28 The microbiomes associated with industrialized countries, like the United States, often have reduced diversity and a higher abundance of Bacteroides when compared to non-industrialized countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A good basic characterisation of the faecal microbiome requires repeated analysis and those could lead to a sub-clustering by what used to be called "enterotype". Although the concept of enterotypes has been questioned, a very recent study demonstrated that the outcome of any dietary manoeuvre for example depends on the starting point represented by distinct enterotypes (Klimenko et al 2022).…”
Section: How To Better Assess the Interplay Of Physiology And Microbi...mentioning
confidence: 99%